Keragaman Burung Pemakan Buah (Avian Frugivora) di Hutan Dataran Rendah Jayapura, Papua - Margaretha Z. Pangau; Supeni Sufaati (Jurnal Biologi Papua, 2012)
Frugivorous birds or avian frugivores play important role in seed dispersal cycle and forest regeneration in forest ecosystem of Papua. Despite the high diversity of avian frugivores dwelling in Papuan rainforest, and the fact that this region faces  alarming rate of forest disturbance, little is known of their current presence in the lowland forest habitat. We surveyed the variety of frugivorous birds in three different habitats of lowland forest in Cyclop Mountains Nature Reserve and Nimbokrang District. The methods used were line and point transects and identification was done during the survey. A total of 36 frugivorous birds from eight families was found in both sites.  There were 33 species of 8 families in Nimbokrang forest and 16 species of 7 families were encountered in the Nature Reserve. The primary forest has high diversity of frugivorous birds compared to that in secondary forest and forest garden. It was found that several species of Family Columbidae such as Macropygia amboinensis, Ducula pinon dan Reindwaedtoena reinwardtii  moved and foraged along the forest edge and also visited degraded areas that still provided vegetation trees and perches. These findings might have importance for forest management and reforestation programmes in Papuan lowland forest.Key words: Frugivorous birds, diversity, lowland forest, Mountain Cyclops Nature Reserve, Nimbokrang.